Quality and readability assessment of online patient information on cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Issue 4 (17th November 2022) - Rouhi, Armaun D.; Ghanem, Yazid K.; Hoeltzel, Gerard D.; Miura, John T.; Aarons, Cary B.; Williams, Noel N.; Dumon, Kristoffel R.; Karakousis, Giorgos C.
Abstract: Background and Objectives: We aim to assess the quality and readability of online information available to patients considering cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS‐HIPEC). Methods: The top three search engines (Google, Bing, and Yahoo) were searched in March 2022. Websites were classified as academic, hospital‐affiliated, foundation/advocacy, commercial, or unspecified. Quality of information was assessed using the JAMA benchmark criteria (0–4) and DISCERN tool (16–80), and the presence of a Health On the Net code (HONcode) seal. Readability was evaluated using the Flesch Reading Ease score. Results: Fifty unique websites were included. The average JAMA and DISCERN scores of all websites were 0.72 ± 1.14 and 39.58 ± 13.71, respectively. Foundation/advocacy websites had significantly higher JAMA mean score than commercial ( p  = 0.044), academic ( p  < 0.001), and hospital‐affiliated websites ( p  = 0.001). Foundation/advocacy sites had a significantly higher DISCERN mean score than hospital‐affiliated ( p  = 0.035) and academic websites ( p  = 0.030). The HONcode seal was present in 4 (8%) websites analyzed. Readability was difficult and at the level of college students. Conclusions: The overall quality of patient‐oriented online information on CRS‐HIPEC is poor and available resources may not be comprehensible to the general public. Patients seeking information on CRS‐HIPEC should be directed to sites affiliated with foundation/advocacy organizations.